2019
DOI: 10.1007/s12520-019-00859-8
|View full text |Cite
|
Sign up to set email alerts
|

Lithic refitting and the analysis of Middle Palaeolithic settlement dynamics: a high-temporal resolution example from El Pastor rock shelter (Eastern Iberia)

Abstract: Archaeostratigraphic study of the Stratigraphic Unit IV from the Middle Palaeolithic site of El Pastor (Eastern Iberia) has resulted on the definition of high-resolution analytical units mostly corresponding to Bmicro-palimpsests^formed during more than a single human occupation. Analysis of these anthropogenic assemblages has suggested their interpretation as remains from several short-term occupations performed by MIS 3-4 Neanderthals. In this paper, we present an evaluation of this interpretative proposal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…Reviewing the upper Pleistocene sites on the Iberian Peninsula, we found caves such as Axlor (Rios-Garaizar, 2017; Gómez-Olivencia et al, 2018), El Castillo (Bernaldo et al, 2014), Cueva Morín (Maillo-Fernández et al, 2014), Esquilleu (Cuartero et al, 2015; Baena-Preysler et al, 2019), Prado Vargas (Navazo and Díez, 2008), Arrillor (Iriarte-Chiapusso et al, 2019), Jarama VI (Jordá-Pardo et al, 2014), Gabasa (Montes and Utrilla, 2014), Abric Romaní (Marín et al, 2017), La Arbreda (Lloveras et al, 2018), Teixoneres (Rosell et al, 2017), Abric del Pastor (Machado et al, 2019), Bolomor (Sañudo et al, 2016), Cova Negra (Martínez Valle et al, 2016), El Salt (Leierer et al, 2019), Bajondillo (Cortés-Sánchez et al, 2019), and Boquete de Zafarraya (Barroso et al, 2014), among others, have shown several levels of Neanderthal occupation. However, most of them have been interpreted as short-term occupations separated by unoccupied gaps during which many of these caves were occupied bycarnivores.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the upper Pleistocene sites on the Iberian Peninsula, we found caves such as Axlor (Rios-Garaizar, 2017; Gómez-Olivencia et al, 2018), El Castillo (Bernaldo et al, 2014), Cueva Morín (Maillo-Fernández et al, 2014), Esquilleu (Cuartero et al, 2015; Baena-Preysler et al, 2019), Prado Vargas (Navazo and Díez, 2008), Arrillor (Iriarte-Chiapusso et al, 2019), Jarama VI (Jordá-Pardo et al, 2014), Gabasa (Montes and Utrilla, 2014), Abric Romaní (Marín et al, 2017), La Arbreda (Lloveras et al, 2018), Teixoneres (Rosell et al, 2017), Abric del Pastor (Machado et al, 2019), Bolomor (Sañudo et al, 2016), Cova Negra (Martínez Valle et al, 2016), El Salt (Leierer et al, 2019), Bajondillo (Cortés-Sánchez et al, 2019), and Boquete de Zafarraya (Barroso et al, 2014), among others, have shown several levels of Neanderthal occupation. However, most of them have been interpreted as short-term occupations separated by unoccupied gaps during which many of these caves were occupied bycarnivores.…”
Section: Discussionmentioning
confidence: 99%
“…Even in archaeological contexts of high temporal resolution, each stratigraphically-expressed palimpsest is acknowledged to integrate successive occupation events (i.e. Julien et al 1992;Vaquero 2008Henry 2012;Vaquero et al 2012a;Chacón et al 2015;Machado et al 2013Machado et al , 2019Mallol et al 2019;Real et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hearths are key features for working towards the goal of dissecting the micropalimpsests (e.g. Machado et al 2013Machado et al , 2019Sañudo et al 2012), because the top of the burnt soils represent occupation surfaces.…”
Section: Lithic Analysismentioning
confidence: 99%
“…Methodologically, this has been approached through spatial analysis by combining archaeostratigraphy and lithic refitting to identify specific knapping sequences and intra-site dynamics (e.g. Bourguignon et al 2008;López et al 2017;Machado et al 2013Machado et al , 2019Nerudová and Neruda 2017;Romagnoli and Vaquero 2016;Sañudo et al 2016;Sumner and Kuman 2014;Takakura 2018;Vaquero 2008;Vaquero et al 2012bVaquero et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation